KONTRIBUSI DAYA LEdAK OTOT TUNGKAI DAN KOORDINASI MATA-KAKI DENGAN HASIL TENDANGAN KE GAWANG DALAM PERMAINAN SEPAKBOLA PADA TIM SMAN 3 SUMBER JAYA KECAMATAN SINGINGI HILIR - Agust, Kristi; ', Zulheri; ', Saripin (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
ABSTRACT, Background problem in this research is not optimal yet shooting in football which is owned by Tim SMAN 3 Sumber Jaya. This is presumably because of explosive power leg muscle factor and eye-foot coordination. Therefore, the purpose of this study was to determine whether there is a contribution of explosive power leg muscle and eye-foot coordination with shooting in football. This type of research is correlational comparing the measurement results of two different variables in order to determine the degree of correlation between these variables. The data were obtained from the standing broad jump test, eye-foot coordination test and shots on goal test. Based on data analysis of explosive power leg muscle has contributed to shooting in football on a team of SMA Negeri 3 Sumber Jaya Singingi Hilir District 44%, marked by the results obtained by the rhit (0.66)> rtab (0361). From the results obtained eye-foot coordination has contributed to shooting in football on team of SMA Negeri 3 Sumber Jaya Singingi Hilir District 16%, marked by the results obtained by the rhit (0.40)> rtab (0361). There are contributing jointly between the explosive power leg muscle and eye-foot coordination with the shooting in football on Team of SMA Negeri 3 Sumber Jaya Singingi Hilir District 49%, is characterized by the results obtained rcount 0.70> rtable 0361.Keywords : Explosive Power Leg Muscles, Eye-Foot Koordination, Shooting